Dynamic characteristics of the hydrogen injector-ejector unit in a PEM fuel cell system - Jiquan Han; Yuhang Chen; Zihui Pang; Jianmei Feng; Anna Diao; Yanchen Yao; Xueyuan Peng (Case Studies in Thermal Engineering)
The ejector, as a fluid-dynamics controlled passive component, is a promising hydrogen recirculation device in proton exchange membrane (PEM) fuel cell systems. Nevertheless, its performance is significantly affected by dynamic operating conditions and the behavior of the injector. This study investigates the dynamic performance of an ejector integrated with a hydrogen injector in a 100 kW PEM fuel cell system. A dynamic computational fluid dynamics (CFD) model of the integrated injector-ejector unit is developed using a dynamic mesh method and validated through theoretical analysis and experimental data. A thorough analysis of the global performance and local fluid flow characteristics of the injector-ejector unit is conducted. The results show that the hydrogen injector, with a throat diameter of 2.00 mm, exhibits an adjustable linear flow range from 0 to 1.62 g/s under an inlet pressure of 2.0 MPa. Additionally, the primary mass flow rate can be linearly regulated by adjusting the valve gap, while the secondary mass flow rate exhibits asynchronous behavior with the primary flow. The velocity and temperature distributions within the injector-ejector unit undergo significant changes under dynamic conditions. These findings contribute to optimizing the design and control strategies of hydrogen supply components in PEM fuel cell systems.